HERRERA GUEVARA, A. (2020), Bioética postsecular e interespecífica: ciencia, ética y cultura en el siglo XXI, Madrid/Oviedo, Catarata. - Alicia García Álvarez (Daimon, 2024)
Reseña de HERRERA GUEVARA, A. (2020), Bioética postsecular e interespecífica: ciencia, ética y cultura en el siglo XXI, Madrid/Oviedo, Catarata.